Penerapan Sistem Hidroponik sebagai Solusi Pemanfaatan Lahan Perkotaan di RT 33 Muara Rapak Kota Balikpapan - Gad Gunawan; Alfian Djafar; Hadhimas Dwi Haryono; Gofind Hasoloan; Lantiunga Celine Agvi Sanchia; Rahma Sarita Dewi; Faadhilah Faadhilah; Hasyer Kamal Baron Wicaksono; Anzan Aulia Yahya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Hydroponics is an agricultural system that use water and nutrients as a substitute for soil in cultivating plants. This method is suitable for limited land such as in urban areas which generally do not have sufficient land for conventional cultivation. The area of RT 33 ​​Muara Rapak is one of the areas in Balikpapan City which of course has limited land. For this reason, after coordinating with local residents, the right collaboration will be carried out in making a hydroponic system using the Nutrient Film Technique (NFT) method as an alternative solution. The activity begins with socializing the work program, making hydroponic installations, preparing places and sowing seeds, transferring seeds to hydroponic installations, maintenance, harvesting, and training. The result of this activity is that residents know the hydroponic system and are able to practice farming with the hydroponic system. This activity also shows that the hydroponic system shows things that are not difficult to do and can be done by anyone. Thus, even though residents have a narrow area of ​​land, they can still enjoy fresh and healthy vegetables that are grown by themselves.